DAMPAK PEMBANGUNAN PERKEBUNAN KARET-RAKYAT TERHADAP KEHIDUPAN PETANI DI RIAU - IKIN SADIKIN; RUDI IRAWAN (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
Meaning sense of this paper is to explain and to analyze development process (insmallholder rubber sub sector) that have done by the government in Riau Province. Agriculturalsystem which plantation system is a compatible model with in local people. Afterwards for toexplain reality and to phenomenon analysis and what dynamic happen in that development, soanalysis and it’s examine pressured to literacy study and others theory and to use information’s.The development problems appear because of the modernization strategy that applied by thegovernment less accommodating local potential’s, with the result that local societies think that thedevelopment are not for them. And finally, development programs less popular in the societiesand can not supported by the people, so consequences social change not yet.